The dynamic business model framework: Illustrated with renewable energy company cases from Indonesia - Linda M. Kamp; Théo A. J. Meslin; Hanieh Khodaei; Roland Ortt (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
It is important for companies to be able to make their business models dynamic. This enables them to adapt to changing circumstances and remain viable. The aim of this paper is to combine insights from the literature on business models and business model dynamics into a comprehensive dynamic business model framework. The framework that is developed in this paper takes into account various origins of changes in business models (internal or external to the company) and various types of changes in business models (primary or secondary changes and forced changes or strategic choices) and also includes the issue of business model consistency. In order to combine different origins and different types of business model change into one dynamic business model framework, some simplifications of reality were needed. The framework is described in text and shown in a comprehensive picture. The application of the framework to two cases of renewable energy companies in Indonesia shows that the framework is able to capture business model dynamics in a simplified and comprehensive way and that it allows for case study comparison. In a thorough discussion, it is shown how the framework can be adapted to make it better able to represent more complex dynamics.
Keywords: 650; BoP markets; business model; dynamics; entrepreneurship; innovation; renewable energy